Survival and dispersal in a newly-founded temperate Barnacle Goose Branta leucopsis population - van der Jeugd, Henk (Wildfowl, 2013)
Survival rates and dispersal were studied in a newly-founded temperate Barnacle Goose Branta leucopsis population in the Netherlands using marked individuals. Birds were ringed at three localities: two in the Delta area in the southwest of the Netherlands and one in Fryslân in the north. Annual survival decreased during 2004–2012 from c. 95% to c. 75%, probably due to an increase in hunting pressure introduced to reduce the size of the population and its damage to agricultural crops. A decrease in survival should lead to a decline in numbers in the population, but this was not apparent from the summer counts. Natal dispersal was high: 56% of males attempted to breed > 10 km from their natal site, and 38% at > 100 km from their natal area. In females, these figures were 30% and 24%, respectively. A substantial number of male Barnacle Geese most probably emigrate to the large population that breeds along the shores of the Barents Sea, and the Dutch Barnacle Goose population currently is a source, from which restocking of the Barent’s Sea population takes place. Breeding dispersal was low. Disturbance of colonies may influence dispersal as birds from one colony disturbed by foxes showed remarkably high natal and breeding dispersal.